Does Livestock Ownership Affect Animal Source Foods Consumption and Child Nutritional Status? Evidence from Rural Uganda - Azzarri, Carlo; Cross, Elizabeth; Haile, Beliyou; Zezza, Alberto (World Bank Group, Washington, DC, 2014)
In many developing countries, consumption of animal source foods among the poor is still at a level where increasing its share in total caloric intake may have many positive nutritional benefits. This paper explores whether ownership of various livestock species increases consumption of animal source foods and helps improve child nutritional status. The paper finds some evidence that food consumption patterns and nutritional outcomes may be affected by livestock ownership in rural Uganda. The results are suggestive that promoting (small) livestock ownership has the potential to affect human nutrition in rural Uganda, but further research is needed to estimate more precisely the direction and size of these effects.